The legal and regulatory framework of transfer pricing in Malaysia - Abu Tariq, Jamaluddin (2023)
Globalisation and the rapid growth of international trade have made intercompany pricing a common consideration for most businesses. Transfer pricing is not illegal or abusive in and of itself. It is a well-known tax principle that a taxpayer has the right to plan his affairs in order to pay less tax than would otherwise be due. However, transfer mispricing, also known as transfer pricing manipulation or abusive transfer pricing, is illegal or abusive. Like other tax jurisdictions, the Malaysian government, through the Inland Revenue Board of Malaysia (IRBM), has enacted transfer pricing guidelines and legislation to combat transfer pricing manipulation and abuse. In 2003, the IRBM issued its first transfer pricing guidelines. Specific transfer pricing provisions were added to the Income Tax Act of 1967 (ITA) later in 2009. Under the new provision, the Director-General of Inland Revenue (DGIR) is empowered to substitute the price of any transactions entered into between related persons to reflect the arm's length price of such transaction. The study's goal is to investigate the legal issues that arise from the implementation of Malaysia's transfer pricing law. This thesis utilises both qualitative case study and legal research methods. Focus was given on two transfer pricing audit cases and the notices of appeal filed by taxpayers with the Special Commissioners of Income Tax (SCIT). In addition, transfer pricing laws and practices in Australia and the United Kingdom were analysed using a comparative research methodology. This study found that the existing transfer pricing law lacks clarity regarding issues pertaining to burden of proof, imposition of penalties, transfer pricing guidelines, arm's length range, breach of natural justice, limitation period, transfer pricing document and transfer pricing method. Subsequently, the study proposed policy changes through amendments to transfer pricing legislation. The recommendations would eventually contribute to the implementation of a comprehensive transfer pricing law in Malaysia